Multi-scale mapping of cultural ecosystem services in a socio-ecological landscape: A case study of the international Wadden Sea Region - Sijtsma, Frans (2019)
Context The governance of international natural World Heritage sites is extremely challenging. In the search for effective multilevel governance there is a need to identify the community of people which have place attachment to the areas, i.e. ‘the community of fans’ at local to international levels. Objectives Focusing on the landscape of the international Wadden Sea coastal area in the Netherlands, Germany and Denmark as a case study, we address three key questions: What is the spatial distribution of the community of fans? How does the size of this community relate to the overlapping communities of locals and actual visitors to the Wadden Sea coastal area? Which parts of the Wadden Sea coastal area are most appreciated by the community of fans, and how does this relate to its formal protection status? Methods We analysed 7650 respondents’ answers to a tri-lateral web survey (the standardized Greenmapper survey) conducted in Denmark, Germany and the Netherlands. Results We estimated that 14 million German, Dutch and Danish citizens can be regarded as the potential—national level—community of fans. The correlation between place or landscape attachment and distance was varied among the three countries. Furthermore, only 37% of the markers placed by fans of the Wadden Sea coastal area are within the protected UNESCO World Heritage limits, suggesting that a broader demarcation could be possible. Conclusions We discuss how the identification of fans can potentially contribute to more effective public involvement in the governance of valuable landscapes.